Cannabinoid hyperemesis syndrome in North America: evaluation of health burden and treatment prevalence. Issue 11 (28th October 2022) - Andrews, Christopher N.; Rehak, Renata; Woo, Matthew; Walker, Ian; Ma, Christopher; Forbes, Nauzer; Rittenbach, Katherine; Hathaway, Joshua; Wilsack, Lynn; Liu, Andy; Nasser, Yasmin; Sharkey, Keith A.
Summary: Background: Cannabinoid hyperemesis syndrome (CHS) is a poorly understood vomiting disorder associated with chronic cannabis use. Aims: To characterise patients experiencing CHS in North America and to obtain a population‐based estimate of CHS treatment prevalence in Canada before and during the Covid‐19 pandemic Methods: Internet survey of 157 CHS sufferers in Canada and the United States. Administrative health databases for the province of Alberta (population 5 million) were accessed to measure emergency department (ED) visits for vomiting, with a concurrent diagnostic code for cannabis use. Three time periods of 1 year were assessed: prior to recreational cannabis legalisation (2017–2018), after recreational legalisation (2018–2019) and during the first year of the Covid‐19 pandemic (2020–2021). Results: Problematic cannabis use (defined as a CUDIT‐R score ≥8) was universal among the survey cohort, and 59% and 68% screening for moderate or worse anxiety or depression, respectively. The overall treatment prevalence of CHS across all ages increased from 15 ED visits per 100, 000 population (95% CI, 14–17) prior to legalisation, to 21 (95% CI, 20–23) after legalisation, to 32 (95% CI, 31–35) during the beginning of the Covid‐19 pandemic ( p  < 0.001). Treatment prevalence among chronic cannabis users was as high as 6 per 1000 in the 16–24 age group. Conclusion: Survey data suggest patients with CHS almost universally suffer from a cannabis use disorder, which has significant treatment implications. Treatment prevalence in the ED has increased substantially over a very short time period, with the highest rates seen during the Covid‐19 pandemic. Abstract : Cannabinoid hyperemesis syndrome mental health burden and treatment prevalence.